Cloudy with a chance of meatballs - Barrett, Judi.; Barrett, Ron (New York : Scholastic Inc., 1993)
Life is delicious in the town of Chewandswallow where it rains soup and juice, snows mashed potatoes, and blows storms of hamburgers--until the weather takes a turn for the worse.
G5
Keywords: Weather -- Fiction; Food -- Fiction